Design, Synthesis, and Biological Evaluation of [1,2,4]triazolo[4,3-a] Pyrazine Derivatives as Novel Dual c-Met/VEGFR-2 Inhibitors - Liu, Xiaobo; Li, Yuzhen; Zhang, Qian; Pan, Qingshan; Zheng, Pengwu; Dai, Xinyang; Bai, Zhaoshi; Zhu, Wufu (Frontiers in Chemistry, 2022)
In this study, a series of [1,2,4]triazolo[4,3-a]pyrazine derivatives were designed, synthesized and evaluated for their c-Met/VEGFR-2 kinase inhibition and antiproliferative activities against tested three cell lines in vitro. Most of the tested derivatives showed moderate to significant potency as compared with Foretinib, with the most promising compound 17l (c-Met IC50= 26.00 nM and VEGFR-2 IC50= 2.6 µM) exhibited excellent antiproliferative activities against A549, MCF-7 and Hela cancer cell lines with IC50 values of 0.98 ± 0.08 µM, 1.05 ± 0.17 µM and 1.28 ± 0.25 µM, respectively. Moreover, compound 17l inhibited the growth of A549 cells in G0/G1 phase in a dose-dependent manner, and induced the late apoptosis of A549 cells. Its intervention on intracellular c-Met signaling of A549 was verified by the result of Western blot. Fluorescence quantitative PCR showed that compound 17l inhibited the growth of A549 cells by inhibiting the expression of c-Met and VEGFR-2 gene, and its hemolytic toxicity to red blood cells was low. Molecular docking and molecular dynamics simulation showed that compound 17l could bind to c-Met and VEGFR-2 protein, and its binding ability was similar with Foretinib.